EPIDEMIOLOGICAL ANALYSIS OF PATIENTS SERVED IN A PUBLIC DENTAL SERVICE FOR PATIENTS WITH SPECIAL NEEDS IN BELÉM - Silva e Silva, Natalia; Brito Cartágenes, Anete; Favacho, Leida; Almeida, Ivone; de Borborema Garcia Pedreira, Juliana; Nelo Pedreira, Erick (Health and Society, 2021)
Objective: In view of the scarcity of research aimed at patients with special needs in our region, this study aims to identify the pathologies, such as age, gender, place of origin and prevalence of caries and periodontal disease in patients enrolled in a public dental service in Belém aimed at the care of people with special needs. Method: Retrospective cross-sectional study, where the data collected in the medical records of the patients enrolled in SIDOPE-UFPA were analyzed. Results: At the end of the data collection, 219 medical records of patients eligible to participate in the study were divided into groups, such as Behavioral Disorder (27.85%), Non-Progressive Brain Encephalopathy (10.5%), Syndromes and malformations (8.7%), Intellective deficit (7.76%), among others. The prevalence of caries was 71.23% and Periodontal Disease was 23.7%; (61.6%) and Belém (62.5%) were the most prevalent place of origin. Conclusion: According to the research, most patients still need treatment, due to the high caries index found, and mainly preventive measures so that these numbers can be reduced in the future. It was also observed the complexity and variety of diseases in the patients enrolled, and the incidence of rare syndromes that should and should be studied more specifically, not only by dentistry, but also by professionals from other areas, emphasizing the importance of care multiprofessional approach to these patients.